The Honorable Peter Stirling and What People Thought of Him - Ford, Paul Leicester, 1865-1902 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Honorable Peter Stirling and What People Thought of Him" by Paul Leicester Ford is a novel written in the late 19th century. The narrative revolves around the character of Peter Stirling, a young man from a humble background who navigates his way through society's expectations and personal relationships, particularly focusing on themes of romance, ambition, and personal growth. At the start of the novel, we are introduced to Mr. Pierce, a dominating conversationalist who dismisses Peter as lacking in romance and imagination due to his upbringing in a mill village. This sets the stage for contrasting perspectives on love and life. Peter is portrayed as earnest and diligent, walking the deck of a yacht as others engage in conversation about romance, while he is mostly an observer. The scene offers a glimpse into his character, suggesting an introspective and serious nature. As the narrative unfolds, we see Peter's struggles with both societal expectations and his internal conflicts regarding love, particularly his feelings for Miss Pierce, leading to significant developments in his journey. (This is an automatically generated summary.)
Release date is 2004-12-30
Juliet Sutherland, Josephine Paolucci, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: New York (N.Y.) -- Fiction; Love stories; Political fiction; Tenement houses -- Fiction; Labor movement -- Fiction